Analysis of Sitting Posture Recognition using Pressure Sensors - Hj Shukor, Ahmad Zaki; Natrah, Nur Atiqa; Afiq, Muhammad Amir; Jamaluddin, Muhammad Herman; Abd Ghani, Zamre; Mohd Shah, Hairol Nizam; Ab Rashid, Mohd Zamzuri (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The sitting posture is one of the most common posture a human being performs. It is usual to see that most of the time, human sit down while doing their activities such as studying, desk work and meetings. Researchers study sitting postures by using sensors such as piezoelectric resistors, fiber optics or even gyroscopes. For our study, we utilize pressure force resistive sensors (FSR) to investigate the sitting posture of students in a lecture environment (classroom). At first we design setup of sensors for measuring pressure during sitting position using pressure sensors, then we analyze sitting posture of the students by using force sensitive resistor sensor and later we investigate the efficiency of the pressure sensing system. We used 11 FSR which is the significantly small amount of sensors at the hipseat and backseat to identify the eight different sitting the posture of the subject at 1 Hz frequency of measurement. Even though the weight of the subjects vary from 40 to 100 kg, the accuracy was acceptable at 90%. Additionally we performed experiments in actual running lecture sessions and later performed quiz to relate the sitting posture with the focus/concentration of students in the class.